The Design of Disease Maps Shapes Perceptions of Threat and Public Policy Preferences - Claudia Engel; Jonathan Rodden; Marco Tabellini (Institute of Labor Economics (IZA), 2021)
Choropleth disease maps have become the main tool for communicating information about the geography of health threats to the public. These maps have the potential to shape perceptions of threat, preferences about policy, and perhaps even behavior, but they are unfortunately often poorly designed and misleading. In a large survey of residents of the U.S. state of Georgia conducted in June 2020, we randomly assigned respondents to view one of two maps produced in the spring of 2020 by the Georgia Department of Public Health. The first is a map of county-level COVID case counts, which generated the false perception that the COVID threat was concentrated almost exclusively in the Atlanta metro area. The second is a map of the case rate per 100,000 people, which clarified that the virus was widespread in much of Georgia. Those who saw the second map were less likely to consider the virus as an urban problem, and more likely to perceive it as a concern for Georgia and its economy. Moreover, respondents from non-metro areas who saw the case rate map were more concerned that they, their friends, or community members might contract the virus. Respondents who saw the case rate map also expressed greater support for policies aimed at mitigating the virus – an effect driven by self-identified Republicans, who were far more skeptical about public health measures to mitigate the spread of the virus in general.
Keywords: I18; I38; 330; COVID-19; policy; maps; public health